A novel fluorescent nitrogen, phosphorus-doped carbon dots derived from Ganoderma Lucidum for bioimaging and high selective two nitrophenols detection. (July 2020) - Tu, Yujiao; Wang, Suping; Yuan, Xiaotian; Wei, Yunlin; Qin, Kunhao; Zhang, Qi; Chen, Xuemei; Ji, Xiuling
Abstract: The highly fluorescent nitrogen, phosphorus carbon dots ( Gl N, P-CDs) and G l CDs deriving from Ganoderma Lucidum were successfully prepared by a simple hydrothermal method. The Gl N, P-CDs exhibited low biotoxicity and good biocompatibility by cell imaging, onion skin staining and in vivo bioimaging. In addition, Gl N, P-CDs and G l CDs showed high selectivity and sensitivity in detecting 2, 4-dinitrophenol (2, 4-DNP) and 4-nitrophenol (4-NP). Good linear range 0–37.5 μM (R 2  = 0.9923) and 0–50 μM (R 2  = 0.9944) for Gl CDs, and 0–30 μM (R 2  = 0.9914) and 0–30 μM (R 2  = 0.9976) for Gl N, P-CDs were obtained, and the low detection limits were 89.77 nM, 100.27 nM ( Gl CDs) and 73.03 nM, 68.09 nM ( Gl  N, P-CDs) for 2, 4-DNP and 4-NP, respectively. It revealed that the inner filter effect dominated in quenching of the Gl CDs and Gl N, P-CDs fluorescent by 2, 4-DNP and 4-NP. The Gl N, P-CDs was successfully used to detect 2, 4-DNP and 4-NP in real water and soil samples. It provided a new insight on the bioimaging application and environmental pollutants detection. Graphical abstract: Schematic of the synthetic route for fluorescent Gl CDs and Gl N, P-CDs, and the applications in cell imaging, onion skin staining, in vivo imaging, 2, 4-DNP and 4-NP detection. Image 1 Highlights: The novel nitrogen, phosphorus-doped CDs deriving from Ganoderma Lucidum were prepared via hydrothermal method. The Gl N, P-CDs possessed a good potential for bioimaging. The Gl N, P-CDs and Gl CDs exhibited high selectivity and sensitivity in detecting 2, 4-DNP and 4-NP.